2009
DOI: 10.1136/thx.2009.116723
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness meditation on cough reflex sensitivity

Abstract: Background: Chronic cough is common, and medical treatment can be ineffective. Mindfulness is a psychological intervention that aims to teach moment-to-moment non-judgemental awareness of thoughts, feelings and sensations. Method: 30 healthy subjects and 30 patients with chronic cough were studied in two sequential trials. For both studies, cough reflex sensitivity to citric acid (C5) was measured on two occasions, with urge to cough rated following each inhalation; between challenges subjects were randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Less is known about the affective processing associated with airways irritation. Of interest, however is that individuals with respiratory disorders such as asthma or chronic cough have a significantly increased risk of developing mood and anxiety disorders, and it seems likely that this would be reflected in altered activity of the network components comprising this cognitive module [25-28]. …”
Section: Suprapontine Cough Pathwaysmentioning
confidence: 99%
“…Less is known about the affective processing associated with airways irritation. Of interest, however is that individuals with respiratory disorders such as asthma or chronic cough have a significantly increased risk of developing mood and anxiety disorders, and it seems likely that this would be reflected in altered activity of the network components comprising this cognitive module [25-28]. …”
Section: Suprapontine Cough Pathwaysmentioning
confidence: 99%
“…Subsequent studies have mostly assessed influences on the intensity of experimentally induced urge-to-cough. For example, viral upper respiratory tract infections and nicotine withdrawal in smokers [10,11] appear to enhance the urge-to-cough, whereas it can be depressed by exercise [12] and mindfulness relaxation techniques [13]. However, none of these studies have acknowledged or reported the somatic sensations evoked by inhaled irritants, only the compulsion to cough.…”
Section: Introductionmentioning
confidence: 97%
“…This awareness may in turn complement other tai chi components that foster improved function (for example, improved posture, relaxation). Recent studies support that mindfulness training can impact interoceptive awareness of key COPD symptoms (such as dyspnea and cough) which may lead to better symptom management [62–64]. Inner awareness of moment-to-moment sensations also helps develop focused attention, providing a tool to manage distracting thoughts [65].…”
Section: Introductionmentioning
confidence: 99%